La información del periodismo digital vs medios de comunicación tradicionales durante el estado de excepción durante el COVID-19 - Cevallos Malagón, Ronny Sebastián (2021)
In this project, the analysis will be applied to be able to know what are the embezzlements that exist in the media, both traditional and digital. Thus, we will understand why certain communication media should not carry that title as such, but should rather be sanctioned by the Organic Law of Communication and in most cases not only be sanctioned but also removed from their functions as an information medium. On the other hand, it will also study how the news of the traditional vs digital media was transmitted in the state of exception due to the COVID-19 virus. This refers to the fact that there was a lot of annoyance on the part of public opinion when they did not know the reality that the country was experiencing in those months. We can see how the traditional media often hid the reality of the situation, but nevertheless, the digital media did show images and real information of the day to day in Ecuador and how people needed help and they lost loved ones due to the lack of average supplies and hospital collapses caused by this virus. This work was carried out by applying the interview and comparative table techniques of two communication media, one being digital and the other traditional. Thus, the analysis could be certified before carrying out the contrasting investigation.